The semaphorins and their receptors as modulators of tumor progression. (November 2016) - Neufeld, Gera; Mumblat, Yelena; Smolkin, Tanya; Toledano, Shira; Nir-Zvi, Inbal; Ziv, Keren; Kessler, Ofra
Abstract: The semaphorins were initially characterized as repulsive axon guidance factors. However, they are currently also recognized as important regulators of diverse biological processes which include regulation of immune responses, angiogenesis, organogenesis, and a variety of additional physiological and developmental functions. The semaphorin family consists of more than 20 genes divided into seven subfamilies, all of which contain the sema domain signature. They usually transduce signals by activation of receptors belonging to the plexin family, either directly, or indirectly following the binding of some semaphorins to receptors of the neuropilin family which subsequently associate with plexins. Additional receptors which form complexes with these primary semaphorin receptors are also frequently involved in semaphorin signalling, and can strongly influence the nature of the biological responses of cells to semaphorins. Recent evidence suggests that semaphorins play important roles in the etiology of multiple forms of cancer. Some semaphorins such as some semaphorins belonging to the class-3 semaphorin subfamily, have been found to function as bona fide tumor suppressors and to inhibit tumor progression by various mechanisms. Because these class-3 semaphorins are secreted proteins, these semaphorins may potentially be used as anti-tumorigenic drugs. Other semaphorins, such as semaphorin-4D, function as inducers of tumor progression and represent targets for the development of novel anti-tumorigenic drugs. The mechanisms by which semaphorins affect tumor progression are diverse, ranging from direct effects on tumor cells to modulation of accessory processes such as modulation of immune responses and inhibition or promotion of tumor angiogenesis and tumor lymphangiogenesis. This review focuses on the diverse mechanisms by which semaphorins affect tumor progression.